(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The present study aims studying the influences of treatment with methanol watery leaf extracts of Calotropis procera on Fasting blood glucose and Insulin level in alloxan induced diabetic male rats. phytochemical analysis of leaves extract reveals presence of Glycosides, Tannines, phenols compound, Flavonoids, Coumarins, Resins and terpenes. Also methanol watery leaf extracts of Calotropis procera dose 250 and 500mg/kg body weight showed significant lowering in the blood glucose from 348.16 ± 36.67 to 169.33 ±21.80 after 45 day of treatment. While showed non-significant enhancement in fasting serum Insulin level.